Investigation of Rocket Effect in BRC 18 using Gaia EDR3 - Saha Piyali; Gopinathan M; Ojha DK; Sharma Neha (Oxford University Press, 2022)
Bright-rimmed clouds (BRCs) are ideal candidates to study radiation-driven implosion mode of star formation as they are potential sites of triggered star formation, located at the edges of HII regions, showing evidence of ongoing star formation processes. BRC 18 is located towards the eastern edge of relatively closer (similar to 400 pc) H II region excited by lambda Ori. We made R-band polarimetric observations of 17 candidate young stellar objects (YSOs) located towards BRC 18 to investigate any preferred orientation of the discs with respect to the ambient magnetic field and the direction of energetic photons from lambda Ori. We found that the discs are oriented randomly with respect to the projected magnetic field. Using distances and proper motions from the Gaia EDR3 of the candidate YSOs, we investigated the possible acceleration of BRC 18, away from lambda Ori due to the well-known 'Rocket Effect', by assuming that both the candidate YSOs and BRC 18 are kinematically coupled. The relative proper motions of the candidate YSOs are found to show a trend of moving away from lambda Ori. We computed the offset between the angle of the direction of the ionization front and the relative proper motion of the candidate YSOs and found it to lie close to being parallel to each other. Additionally, we found 12 sources that are co-moving with the known candidate YSOs towards BRC 18. These co-moving sources are most likely to be young and are missed in previous surveys conducted to identify potential YSOs of the region.